Pier pressure: 23 years of incidental sea turtle captures at recreational fishing piers along Florida’s Gulf coastline - Brannum, Robby J.; Minch, Karrie; Wideroff, Morgan; Koperski, Meghan E.; Shea, Colin P.; Foley, Allen M.; Trindell, Robbin N. (Frontiers in Marine Science, 2025)
Incidental captures of sea turtles during fishing activities affect their populations worldwide. Previous research has documented the impacts of commercial fisheries in nearshore and offshore waters, and research-based minimization measures are now required to reduce sea turtle take. However, incidental captures of juvenile-to-adult sea turtles also occur in recreational fisheries in nearshore and inshore waters, although the magnitude and distribution of these events are poorly understood. We analyzed Florida Sea Turtle Stranding and Salvage Network (STSSN) reports between 2000 and 2022 to identify sea turtles incidentally captured by recreational anglers from fishing piers along Florida’s Gulf coastline. We used a negative binomial regression model to quantify temporal and spatial changes in the mean number of pier-captured sea turtles reported at Gulf piers over the 23-year study period. There were 452 documented incidents of loggerheads (Caretta caretta), green turtles (Chelonia mydas), and Kemp’s ridleys (Lepidochelys kempii) hooked at 33 different piers. Juvenile and subadult turtles of all three species were pier-captured as well as adult loggerhead and Kemp’s ridley turtles. The number of turtles for each of the three species captured varied over time, but overall the number of reported captures increased regionally over the 23-year study. Most turtles captured and recovered at recreational fishing piers were successfully rehabilitated and released back to the wild (84.7.%). The observed increases in sea turtle pier capture reports likely reflect some combination of increased turtle numbers in the nearshore environment, increased use of piers as foraging habitat, and increased reporting requirements and effort. This analysis offers insights into the complex interactions between sea turtles and pier-based recreational fishing in the Gulf and could help inform conservation efforts while supporting responsible recreational fishing practices.